ACCOUNTABILITY OF THE DEPARTMENT OF TRANSPORTATION FOR SUPERVISION OF ROADSIDE PARKING IN THE LUWUK DISTRICT AREA - Fadli Sandewa (Sean Institute, 2023)
This research will be carried out at the Banggai Regency Transportation Service. The aim is to find out the extent of the Transportation Service's Accountability for Supervision of Parking on the Roadside in the Luwuk District, Banggai Regency. In this study, the data collection techniques that the authors used were interview techniques, observation techniques, questionnaires, and documentation. The types and sources of data used in writing this research are primary data and secondary data. The population in this study were all Banggai Regency Transportation Service Employees. In taking the sample, the researcher used a saturated sampling technique so that the research sample totaled 150 people. The scale used to measure each indicator is using a Likert scale. To analyze and test the data the author uses a qualitative analysis method which will be carried out based on percentage descriptive statistics. Based on the results of the Accountability of the Banggai Regency Transportation Office for Supervision of Parking on the Roadside in the Luwuk District Area. has a response reaching 67% of responses and is included in the good criteria.